Implementation of Character Education in History Learning - Diah Karmina; Katerina Dalakoura; Lydiah Njoki Wachira (Cahaya Ilmu Cendekia Publisher, 2023)
The approach used in this study is a qualitative approach with purposive sampling of data sources. While the data collection techniques used include observation and interviews. The data analysis technique used is the Miles and Huberman method which includes data collection, data reduction, data presentation and verification. The results showed that (1) the history teacher's readiness in implementing character education was good by preparing the syllabus and lesson plans, (2) the implementation of character education was not optimal because the teacher had not included character education assessment instruments, but it was done well because it was in accordance with the syllabus and lesson plans that were inserted with an explanation of the values of the nation's character, (3) the obstacles experienced by teachers, namely: time is so short, the community environment is not conducive, electronic media, learning models, and costs to support character education activities, (4) perception and appreciation / student responses to the implementation of character education have been good as evidenced by good character and supported by the strictness of the rules from the school.